(untitled) (Global Journal of Human-Social Science, 2016)
The purpose of the study was to examine the educational attainment rates of Hispanic and Black students in Texas 2-year colleges from the 2009 through the 2014academic years The number of career colleges in Texas increased from 52 in the 2009 academic year to a total of 80 career colleges in the 2014 academic year Along with increases in the number of career colleges the total numbers of Hispanic and Black students who attained a certificate or adegree during this time period also increased The average number of Hispanic and Black students who obtained a degree or certificate from Texas 2- year career colleges rose steadily until reaching a high of 155 32 degrees and orcertificates attained for Hispanic students in the 2011 academic year and a high of 64 19 degrees and or certificatesattained for Black students in the 2012 academic year Overtwice as manyHispanic students than Black students obtained a degree or certificate from Texas career colleges in the 6-year period analyzed in this investigation Over the 6-year period of the 2009 through the 2014 academic years the average percentage of Hispanic and Black students who obtained a degree or certificate from Texas 2-year career colleges fluctuated Implications of these results as well asrecommendations for future research were discussed